Understanding and addressing gender-based violence through qualitative research - Velasquez, Maria Paula (2025)
This Learning Note explores how qualitative research can illuminate and address gender-based violence (GBV) in contexts affected by climate change, conflict, and migration. It highlights the value of participatory, gender-sensitive, and intersectional approaches in revealing how social, environmental, and power dynamics shape vulnerability and resilience. Emphasizing ethical awareness, trust-building, and researcher care, the Note calls for integrating GBV risk mitigation into research design and promoting women’s agency in community and environmental decision-making. It underscores that empathy and ethics are essential for transforming evidence into meaningful, equitable action.